Wallenstein's Camp: A Play - Schiller, Friedrich, 1759-1805 (Salt Lake City, UT : Project Gutenberg, 2004)
"Wallenstein's Camp: A Play" by Friedrich Schiller is a dramatic prologue written in 1799. Set during the Thirty Years' War in 1633, this work introduces the legendary general Albrecht von Wallenstein through the eyes of his diverse mercenary soldiers. The troops praise their commander's leadership and the freedoms he grants them, while tensions simmer over the Holy Roman Emperor's demand to redistribute forces. This opening piece sets the stage for Wallenstein's eventual confrontation with imperial authority and his fateful downfall. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Wallenstein_(trilogy_of_plays)
Release date is 2004-12-08
Produced by Tapio Riikonen and David Widger
Keywords: Wallenstein, Albrecht Wenzel Eusebius von, Herzog von Friedland, 1583-1634 -- Drama